Case Report: De novo DDX3X mutation caused intellectual disability in a female with skewed X-chromosome inactivation on the mutant allele - Sun, Yixi; Qian, Yangwen; Sun, Hai-Xi; Chen, Min; Luo, Yuqin; Xu, Xiaojing; Yan, Kai; Wang, Liya; Hu, Junjie; Dong, Minyue (Frontiers in Genetics, 2022)
Skewed XCI plays an important role in the phenotypic heterogeneities of many X-linked disorders, even involving in diseases caused by XCI–escaping genes. DDX3X-related intellectual disability is more common in females and less common in males, who usually inherit from unaffected heterozygous mothers. As an X inactivation (XCI) escaping gene, the role of skewed XCI in the phenotype of DDX3X mutant female is unknown. Here we reported a DDX3X: c.694_711dup18 de novo heterozygous mutation in a female with intellectual disability on the maternal X chromosome on the basis of SNPs detected by PCR-sanger sequencing. AR assay revealed that the maternal mutant X chromosome was extremely inactivated in the proband. Using RNA sequencing and whole-exome sequencing, we quantified allelic read counts and allele-specific expression, and confirmed that the mutant X chromosome was inactive. Further, we verified that the mutant DDX3X allele had a lower expression level by RNA sequencing and RT-PCR, and the normal and mutated DDX3X expression accounted for respectively 70% and 30% of total. In conclusion, we found a symptomatic female with extreme skewing XCI in the DDX3X mutant allele. It was discovered that XCI in the mutant allele was insufficient to reverse the phenotype of DDX3X-related neurodevelopmental disorder. It contributed to a better understanding of the role of skewed XCI in phenotypic differences, which can aid in the genetic counseling and prenatal diagnosis of disorders in females with DDX3X defects.